The Relationship Between Followership Style and Organizational Commitment: A Study PT PLN (Persero) - , Iccha Petsiwi, Dr. Tarsisius Hani Handoko, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Followership does matter within an organization, yet seems to be uninteresting and unexplored topic. Following Kellyâs (1988) idea, there are two dimensions of followership, namely active engagement and independent critical thinking. Active engagement relates to how individual pioneers actions. They will try to ensure functioning and activity as in the form of responsibility. This, they initiate valuebased action that they act initiatively, courageously, and assume ownership at last. While independent critical thinking relates to how individual are eager to be innovative and creative by thinking independently without depending on the leader, offering criticism to him/her when necessary, or let them evaluate how task is being performed. Through this, followers likely identify with their organization once they perform. Therefore, it was argued that these two dimensions of followership were correlated with organizational commitment (both affective and normative commitment). This study surveyed 119 employees of PT PLN (Persero) North Surabaya. To collect the data, purposive sampling was used and the questionnaire was distributed to permanent employees who have at least worked a year within the company. Test analysis of the data used multiple regression. The result showed that active engagement has significant relationship with both affective commitment and normative commitment. While independent critical thinking has insignificant relationship with both affective commitment and normative commitment. The relationship between followership style and organizational commitment was also discussed as an additional analysis.